Development of a testing facility for modelling cooling technique - Jaafar, Abdul Aziz; Abu Talib, Abd Rahim; Abdul Rahim, I.; Filipski, Mohammad Nizam; Salit, Mohd Sapuan (Federation of Engineering Institutions of Islamic Countries, 2006)
Development of a low speed testing facility, adopting blow tunnel configurations and specialised working section arrangements for general purposes flow and heat transfer investigations, is described. This article reports a preliminary design of the testing facility within the constraint of fabrication cost and space availability for investigation of a film cooling technique. The cooling technique is modelled as a tangential jet flow in a sudden expansion channel and the dimensional analysis was adopted for formulating possible functional relationships between testing parameters and cooling performances. Although slight improvements have been made to the range of testing conditions, modifications of the previous testing facility show an encouraging result in the flow properties entering the working section.